2016
DOI: 10.1016/j.shaw.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Mortality Across Broad Occupational Groups in Greece: A Descriptive Study

Abstract: BackgroundSeveral studies have investigated the relationship between specific occupations and suicide mortality, as suicide rates differ by profession. The aim of this study was to investigate suicide mortality ratios across broad occupational groups in Greece for both sexes in the period 2000–2009.MethodsData of suicide deaths were retrieved from the Hellenic Statistical Authority and comparative mortality ratios were calculated. Occupational classification was based on the International Classification of Occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 41 publications
3
27
0
2
Order By: Relevance
“…Most of the studies included in the meta-analysis were conducted in English-speaking countries: including Australia and New Zealand (N=8) (20,29,35,39,49,50,52,58), the United States and Canada (N=8) (24,30,34,36,38,47,57,60), and the United Kingdom (N=5) (19,22,33,54,56). Others originated from European Nordic countries (N=5) (26,28,37,53,59), France (N=2) (51, 55), Japan (N=2) (23,31), and Greece (N=1) (25). One study was based on both French and Spanish samples (32).…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies included in the meta-analysis were conducted in English-speaking countries: including Australia and New Zealand (N=8) (20,29,35,39,49,50,52,58), the United States and Canada (N=8) (24,30,34,36,38,47,57,60), and the United Kingdom (N=5) (19,22,33,54,56). Others originated from European Nordic countries (N=5) (26,28,37,53,59), France (N=2) (51, 55), Japan (N=2) (23,31), and Greece (N=1) (25). One study was based on both French and Spanish samples (32).…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
“…The studies used different measures of association: one used CMR (25), three used PMR (19,22,54), eight used SMR (24,47,52,53,55,56,58,60), two used HR (26,59), three used OR (20,30,31) and nine used RR (23,28,29,32,33,(49)(50)(51)57). For five studies, we calculated OR and 95% CI and, for one study, we calculated RR and the 95% CI from raw data (34)(35)(36)(37)(38)(39).…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Было доказано, что непосредственное столкновение со смертью и жестокостью спо собствует формированию чувства вины, сты да, сожалений о совершенном и негативному восприятию себя [8]. Возрастной интервал 30-39 лет представляет наибольший риск со вершения суицида [3,8].…”
Section: факторы и последствия психической дезадаптации у специалистоunclassified
“…Intentional injuries showed a significantly higher rate of hospitalization for "suicide" and "homicide" for low-income inpatients in both fatal and non-fatal injuries. Additionally, previous research has shown that unemployment and specific occupations were also associated with suicide and suicidal behavior [21,22,23,24]. According to the low-income family study conducted by the Ministry of the Interior of Taiwan, 62% of low-income family members have suffered catastrophic illnesses in the past [12].…”
mentioning
confidence: 99%